EXPLORING EFL STUDENTS’ PERSPECTIVES ON CPBL FOR 21ST CENTURY SKILLS DEVELOPMENT - Salsabila Nurhaliza; Deby Dwi Juliani; Khamelia Agustini; Wardah Sri Erza (The Journal of English Literacy Education: The Teaching and Learning of English as A Foreign Language, 2025)
Cooperative project-based learning (CPBL) connects theoretical knowledge to practical application. Engaging in CPBL not only enhances students’ comprehension but also fosters 21st-century skills, which are crucial for navigating challenges in today’s dynamic world. CPBL empowers students to actively participate and feel personally invested in their education by immersing them in authentic learning experiences. This research aims to explore the perspectives of students engaged in CPBL initiatives to illuminate their perspectives on its efficacy in developing essential skills for the modern era. This research, involving 273 students from Sriwijaya University’s English Education Study Program, uses a survey method to explore students’ perceptions and challenges regarding CPBL in fostering 21st century skills. In-depth interviews provided qualitative insights into the impact of CPBL on language development and overall educational experience. The quantitative data were analyzed using SPSS to tabulate respondents’ answers, calculate percentages, and identify patterns, whereas the qualitative data were subjected to thematic analysis. The findings reveal a gap between students’ perceived importance of 21st-century skills and their actual proficiency in applying these skills, the need for enhanced training. Additionally, the interviews highlighted obstacles in collaborative learning, including communication issues and differing perspectives. The findings revealed that although students acknowledged the significance of acquiring 21st-century skills, their comprehension of the skills was somewhat deficient.